THE INSIGHTS OF COMPUTER-AIDED MEASUREMENT SOFTWARE FROM UNDERGRADUATE’S PERSPECTIVES - Wan Mohd Nurdden Wan Muhammad; Ku Mohammad Asyraf Ku Azir; Nur Husnina Abdul Halim; Irma Hanie Ibrahim (Jurnal Penyelidikan Sains Sosial, 2022)
Construction industry players in Malaysia has recognised and adopted Computer-Aided Measurement (CAM) software in in their activities with the objective to improve qualityand accuracy of construction process. CAM software promotes useful and effective resultsespecially in quantity take-off and estimating for construction works and being a component ofBuilding Information Modelling (BIM) ecosystem. Nevertheless, it is important for theconstruction players to be skilful and knowledgeable in operating the CAM software prior tothe extensive adoption of the software for construction projects. As a reflection to the situation,higher learning institutions in Malaysia has progressively embedded CAM software applicationlesson in the undergraduate’s curriculum for students. Hence, this paper discovers the insightsof CAM software application from the student’s perspective. Quantitative research has beenconducted to gather the consensus among students and analysed through statistical analysis.The findings shows that students are optimistic with the CAM software capabilities and lookforward on its application in the real-time profession in the future. It is believed the findingsmanage to raise the attention among other higher learning institutions toward the adoption ofCAM software as well as to address the construction industry players on the undergraduate’sreadiness on the CAM software knowledge and skill in the future.